The transformation of Lithuanian heritage preservation system in 1987–1995 years: between vision and reality - Medvedevienė, Daiva (Journal of Architecture and Urbanism, 2012)
The article analyses the Lithuanian system of the cultural heritage preservation and it’s transformations from the 1987 to 1995. It was evident, that the system, formed during the Soviet era, does not ensure the preservation of the Lithuanian culture heritage. Consequently, after regain of Lithuania independence, the first aim was to form the completely new system of the cultural heritage preservation. The set up goals in this article are to ascertain the factors, which encouraged Lithuanian society to consider the necessity of the formation the new system, to define the initial vision, which in the beginning was seen by the heritage preservationists, to explore the process of the development of the modern Lithuanian heritage preservation system, to define the final results and to compare them with the primary vision. The main question is, did the embodied system correspond to the initial concept? Article in Lithuanian. 1987–1995 m. paveldosaugos transformacijos: tarp vizijos ir tikrovės Santrauka. Straipsnyje nagrinėjama Lietuvos paveldo apsaugos sistemos reformavimo 1987–1995 m. problematika. Sovietiniais metais veikusi paveldo apsaugos sistema buvo neefektyvi ir neužtikrino Lietuvos kultūros paveldo įvairovės išsaugojimo. Todėl jau atgimimo laikotarpiu buvo suvoktas paveldosaugos sistemos reformavimo būtinumas. Straipsnyje siekiama atskleisti, kokios priežastys paskatino visuomenę prabilti apie sistemos reformos būtinumą, kokia buvo regima naujoji paveldo apsaugos sistema ir kaip pavyko ją įgyvendinti, ar galutiniai reformos rezultatai atitiko pradinę viziją? Reikšminiai žodžiai: paveldo apsaugos sistemos reforma, naujoji paveldo apsaugos sistema, paveldo apsaugos įstatymų priėmimas.